2018
DOI: 10.1088/1361-665x/aadaaa
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet entropy based structural damage identification under seismic excitation

Abstract: In this work, an entropy based two-step structural damage identification method under seismic excitation is proposed. The measured signals are decomposed by means of wavelet packet transform, and the wavelet entropies are obtained on the basis of the information entropy theory. In the first step, the damage alarming indices, calculated with the wavelet entropies in undamaged and damaged conditions, are used as samples for Shewhart individuals control chart to alarm the structural damage. In the second step, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Second, frequency‐domain methods use the Fourier, and inverse Fourier transforms to extract features in a given time window, such as frequency response functions (FRFs), 10 power spectral density (PSD), 11 and cepstrum 12 . Frequency‐domain methods only analyze stationary events localized in the time domain; on the other hand, time‐scale domain methods can explore any nonstationary possibility localized in the time domain by employing wavelet transforms to extract the signal features, including wavelet coefficients, 13 wavelet energies, 14 and wavelet entropy 15 . The main advantage of time‐domain methods over frequency‐domain methods is the ability to control nonlinear responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, frequency‐domain methods use the Fourier, and inverse Fourier transforms to extract features in a given time window, such as frequency response functions (FRFs), 10 power spectral density (PSD), 11 and cepstrum 12 . Frequency‐domain methods only analyze stationary events localized in the time domain; on the other hand, time‐scale domain methods can explore any nonstationary possibility localized in the time domain by employing wavelet transforms to extract the signal features, including wavelet coefficients, 13 wavelet energies, 14 and wavelet entropy 15 . The main advantage of time‐domain methods over frequency‐domain methods is the ability to control nonlinear responses.…”
Section: Introductionmentioning
confidence: 99%
“…12 Frequency-domain methods only analyze stationary events localized in the time domain; on the other hand, time-scale domain methods can explore any nonstationary possibility localized in the time domain by employing wavelet transforms to extract the signal features, including wavelet coefficients, 13 wavelet energies, 14 and wavelet entropy. 15 The main advantage of time-domain methods over frequency-domain methods is the ability to control nonlinear responses. However, most time-domain methods require the undamaged state of the structure as the baseline state to compare with damage states.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [ 38 ] defined wavelet entropy, relative wavelet entropy, and wavelet time entropy, and numerical simulation and laboratory experiments showed that these three kinds of wavelet entropy could locate and identify damage; moreover, relative wavelet entropy did not require pre-damage response data. Diao et al [ 39 ] constructed a kind of wavelet entropy to identify structural damage under seismic excitation. They verified the feasibility of wavelet entropy on the basis of model experiments using a numerical simulation of an offshore platform structure and a vibration table.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, entropy, a powerful nonlinear measurement, has been introduced in different fields such as neuroscience (Li et al, 2018a(Li et al, , 2018bWang et al, 2018aWang et al, , 2018b, monitoring of electrical machines (Wu et al, 2018), monitoring of gearboxes (Figlus, 2019), cardiac diseases (Acharya et al, 2018;Kumar et al, 2016), and the health monitoring of simple beams of few structural elements (Diao et al, 2018;Moreno-Gomez et al, 2018), among other fields. Entropy provides a measure of data randomness encountered in a nonlinear and nonstationary time signal (Shannon, 1948), making it an appropriate tool for detecting damage in civil structures because the measured signals can vary according to damage and its severity encountered in the civil structure, thus producing a change in the entropy value.…”
Section: Introductionmentioning
confidence: 99%